James Power Smith papers - Smith, James Power, 1837-1923.
Official Confederate army correspondence, orders, and reports. Includes a report by Capt. William Robertson Garrett on the attack of the 1st Virginia Atillery Regiment, Company F (also known as the Lee Artillery or Williamsburg Light Artillery) on Fort Magruder, Va., May 5, 1862; Gen. John Bell Hood's report on the engagement at Eltham's landing, Va., May 7, 1862; and other reports on the battle of Williamsburg by Lt. Col. J. Thompson Brown, Lt. William Izard Clopton, Capt. James Dearing, Capt. George E. Pickett, Capt. Robert M. Stribling, and Gen. Cadmus M. Wilcox. Also includes reports by Gen. Braxton Bragg on the battle of Chickamauga; letter (1863 February 25) from Gen. Bragg to Gen, Joseph E. Johnston explaining his plan for attack on Franklin, Tenn.; and letter (1863 January 5) from Samuel Preston Moore, Confederate surgeon-general, to James A. Seddon, secretary of defense, relating to pay for soldiers detained in the Confederate Army Medical Dept. Other persons represented include Stephen R. Mallory (Confederate secretary of the navy), Gen. George Henry Thomas, and Gen. C. C. Washburn.
In part, handwritten transcripts.
Confederate army officer and author.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Bragg, Braxton, -- 1817-1876.; Brown, J. Thompson -- 1835-1864.; Clopton, William Izard; Dearing, James, -- 1840-1865.; Garrett, William Robertson, -- 1839-1904.; Hood, John Bell, -- 1831-1879.; Johnston, Joseph E. -- 1807-1891.; Mallory, Stephen R. -- 1813-1873; Moore, Samuel Preston, -- 1813-1889.; Pickett, George E. -- 1825-1875.; Seddon, James A; Stribling, Robert M. -- 1833-1914.; Thomas, George Henry, -- 1816-1870.; Washburn, C. C. -- 1818-1882.; Wilcox, Cadmus M. -- 1824-1890.; Confederate States of America. -- Army. -- Medical Department; Confederate States of America. -- Army. -- Virginia Artillery Regiment. 1st. -- Company F; Chickamauga, Battle of, Ga., 1863.; Franklin, Battle of, Franklin, Tenn., 1864.; Fort Magruder (Va.); Williamsburg, Battle of, Williamsburg, Va., 1862.; Georgia -- History -- Civil War, 1861-1865 -- Campaigns; Tennessee -- History -- Civil War, 1861-1865 -- Campaigns; United States -- History -- Civil War, 1861-1865 -- Campaigns; United States -- History -- Civil War, 1861-1865 -- Medical care; Virginia -- History -- Civil War, 1861-1865 -- Campaigns; Army officers, Confederate; Authors